765 The impact of mind wandering on road safety. (1st September 2016) - Galéra, Cédric; Gil-Jardinet, Cédric; Née, Mélanie; Salmi, Rachid; Orriols, Ludivine; Contrand, Benjamin; Lagarde, Emmanuel
Abstract : Background: Mind wandering before the crash has been associated with a heightened probability of being responsible for a crash. Yet measurement bias (desirability bias) may explain this association. To progress in the understanding of mind wandering in road safety we sought to assess the relationship between mind wandering trait (a persistent characteristic of the individual) and state (just before the crash) and the risk of being responsible for a road crash. Methods: We conducted a responsibility case-control study in an adult emergency department of the Bordeaux university hospital in France, (2013–2015). Participants were 954 drivers injured in a road crash. Measures were responsibility for the crash, mind wandering (trait/state), external distraction, alcohol use, psychotropic drug use, and sleep deprivation. Results: Intense mind wandering (highly disrupting/distracting content) state was associated with responsibility for a traffic crash (odds ratio 2.3, 95% confidence interval 1.5 to 3.5). Mind wandering trait was also associated with responsibility for a traffic crash (odds ratio 1.8, 95% confidence interval 1.3 to 2.5). Conclusions: Mind wandering, whether just before the crash or as a general propensity characteristic of the individual, is associated with a higher risk of being responsible for crashes. Mind wandering is a deleterious source of inattention on the road.